Kesejahteraan Psikologis Pada Remaja dengan Orang Tua Merantau - Dhea Octa Ningtyas; Laila Putri Ananda; Luthfi i Sri Handayan; Ruwita Erinasari; Hengki Hendra Pradana (Psycho Aksara : Jurnal Psikologi, 2023)
This study aims to determine the psychological well-being of adolescents whose parents live abroad. This study uses a qualitative method with a case study approach, involving 6 participants, consisting of 3 subjects and 3 significant others with the criteria that the subject is still a teenager or has passed the teenage stage and one or all of the subject's parents work outside the area/migrate. Data collection techniques used interview techniques using 10 questions for the subject and 9 questions for significant others, and these questions were taken based on factors that affect psychological well-being. The results show that adolescents who are abandoned by one or all of the subject's parents working outside the area/migrating have low psychological well-being. In this study, the psychological well-being of adolescents whose parents live abroad is at a low level, meaning that further treatment is needed so that the psychological well-being of adolescents becomes high. If adolescents whose parents migrate have high psychological well-being in this case, it can help adolescents pass developmental tasks, face challenges, live their lives happily, calmly and be able to overcome all the problems they face.